Levels, severity, and determinants of stunting in children 0-59 months in Afghanistan: Secondary analysis of Multiple Indicator Cluster Survey, 2022-23. - William Joe; Atma Prakash; Said M Yaqoob Azimi; Melanie Galvin; Zivai Murira; Gustavo Nicolas Paez Salamanca; Vani Sethi (PLOS Global Public Health)
Childhood stunting is a critical nutritional concern for Afghanistan. Prioritizing development assistance toward child nutrition requires recent estimates on child stunting and timely insights on determinants at national and sub-national levels. This study addresses this gap by estimating the prevalence and determinants of stunting and severe stunting in children under-five using the latest publically available data. The recent wave of Afghanistan Multiple Indicator Cluster Survey (MICS 2022-23) was analyzed to estimate the prevalence of stunting (height-for-age Z-score <-2SD) and severe stunting (<-3SD) by demographic and socioeconomic characteristics. The predictors of stunting and severe stunting outcomes were examined using multivariate logistic regression analyses with four domains of independent variables - child, maternal, and household characteristics and complementary feeding practices. In Afghanistan, 44·5% of children were stunted and 21.6% were severely stunted. The southern region has the highest burden of stunting (55%). Under-five females were less likely to be stunted than males [OR 0·89, 95% CI (0·84, 0·95)]. The likelihood of stunting increased with age of the child. Lack of maternal education, lower wealth quintiles, no exposure of the mother to mass media, and poor dietary diversity were the key predictors of stunting. Determinants of severe stunting mirrored those of stunting, with the additional risk for 24-59 months age group and higher birth order. Socioeconomic status, maternal education, child age, birth order, dietary practices, and geographical location were key determinants of stunting. Targeted interventions addressing poverty, education for women, family planning, and improved nutrition are crucial to reducing childhood stunting in Afghanistan.